Traditional Processing of Sikapa (Dioscorea Hispida) as an Alternative Food Source in the Dry Season - Andriyana Abdullah; Haniarti; Muhammad Ikram; Dirman Dirman (Tadulako University, 2026)
The traditional processing of Sikapa (Dioscorea hispida) is a form of adaptation by rural communities to meet the need for alternative food during the dry season. This study aims to document the stages of traditional Sikapa processing carried out by the community of Tapuan Hamlet, Tungka Village, Enrekang Regency. The study used a qualitative descriptive approach through direct observation and visual documentation without conducting laboratory tests. The results showed that the processing process includes nine main stages, starting from raw material selection, peeling, slicing, soaking in salt water, further soaking in running water, steaming, drying, to the final processing into Sikapa Chips and Sokko Sikapa. All stages are carried out consistently based on local knowledge passed down from generation to generation. This management produces food products that are shelf-stable, thus potentially supporting food security during the dry season. This documentation provides a factual description of community practices and serves as a basis for further research that assesses chemical aspects and food safety in more depth.